Influence of graduates’ personality traits towards employability in hospitality and tourism industry / Aisyah Anas and Nur Suhana Md Nor - Anas, Aisyah; Md Nor, Nur Suhana (2018)
Service has become a profound contributor to national income and this industry is rapidly expanding as more people especially graduates is seeking jobs in the said sector. It is difficult to pinpoint the main reason why the population is attracted to this industry as no studies have yet to reveal such factors. Surely, passion in providing service could not be the sole motivator into chasing jobs in this industry? What does it take for one to acquire a place in a hospitality sector? What is the employability that hospitality job seekers possess? Based on the studies made by World Travel and Tourism Council, the number of graduates who will seek positions in hospitality in the year 2020 will increase by 67,324 as compared with 2010. It is apparent from the statement that employability amongst job seekers has increased significantly. It is possible but not entirely plausible that graduates with the ‘perfect’ personality traits are the biggest factor that the hospitality accepts more people into this industry. Therefore, it is prudent to determine which personality traits that graduates possess that contributes to their getting employed in the hospitality industry. The Big Five model is the researchers’ preferred form of measurement to determine such personality traits that contribute to graduates’ employability in the hospitality industry.